PLAGUE AND THA'UN IN ACEHNESE SOCIETY: A STUDY OF MANUSCRIPTS IN ACEH - Nurulfitria Fauzi; Misri A. Muchsin (Indonesian Journal of Islamic History and Culture, 2021)
This study aims to examine various kinds of plague and tha'un that existed before and during the early era of Islam in the Arabian Peninsula. In the following years there were also many outbreaks around the world causing many deaths. The purpose of this study is to determine the content and information of the manuscripts on the strategies facing plague especially in Aceh and how to treat and prevent outbreaks among Acehnese society. This research uses a qualitative method with a philological approach or manuscript study which includes manuscript collection, description, transliteration, manuscript editing and content analysis. The results of the study show that plague and tha'un in the public's perception are two different diseases. This study also found in the records that the first outbreak in Aceh was in the second phase of the Dutch aggression, which was in the early 1874. This study also revealed the history of cholera, beriberi and smallpox outbreaks. In addition, the manuscript also mentioned various ways of dealing with epidemics in the community including tulak bala, praying to get rid of ill omen.